2018
DOI: 10.1016/j.pharmthera.2018.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Canine sarcomas as a surrogate for the human disease

Abstract: Pet dogs are becoming increasingly recognized as a population with the potential to inform medical research through their treatment for a variety of maladies by veterinary health professionals. This is the basis of the One Health initiative, supporting the idea of collaboration between human and animal health researchers and clinicians to study spontaneous disease processes and treatment in animals to inform human health. Cancer is a major health burden in pet dogs, accounting for approximately 30% of deaths a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
80
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(85 citation statements)
references
References 227 publications
(286 reference statements)
4
80
1
Order By: Relevance
“…), combined them in the therapy may increase the success of ttreatment and usefull for detecting of efficacy and toxicity of them [7]. The most important is the basis of the One Health initiative, supporting the idea of collaboration between human and animal health researchers and clinicians to study spontaneous disease processes and treatment in animals to inform human health [5].…”
Section: Brain Tumours: Cancer That Originates In the Brain Cells [4]mentioning
confidence: 99%
See 1 more Smart Citation
“…), combined them in the therapy may increase the success of ttreatment and usefull for detecting of efficacy and toxicity of them [7]. The most important is the basis of the One Health initiative, supporting the idea of collaboration between human and animal health researchers and clinicians to study spontaneous disease processes and treatment in animals to inform human health [5].…”
Section: Brain Tumours: Cancer That Originates In the Brain Cells [4]mentioning
confidence: 99%
“…Approximately 1 in 4 dogs will, at some stage in their life, develop neoplasia. Almost half of dogs over the age of 10 will develop cancer [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Despite their relatively low occurrence, sarcomas remain a significant clinical challenge with high mortality rates, particularly among adolescents . In dogs, soft tissue and bone sarcomas occur with high frequency in comparison to people . Absolute and relative incidence of sarcomas in dogs is unknown, as formal registries do not exist to accurately capture this data.…”
Section: Introductionmentioning
confidence: 99%
“…Absolute and relative incidence of sarcomas in dogs is unknown, as formal registries do not exist to accurately capture this data. Previous literature has suggested that soft tissue sarcomas account for 9% to 15% of all cutaneous and subcutaneous tumours with between 27 000 to greater than 95 000 dogs diagnosed with a soft tissue sarcoma each year in the United States; this is likely an underestimate and based on owners who seek a diagnosis. When considering vascular tumours, angiosarcoma in humans is a subset of soft tissue sarcomas that accounts for approximately 1% to 2% of all soft tissue sarcomas (~300 patients each year) and carries an overall poor prognosis with a high metastatic rate .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation